1995
DOI: 10.1016/s0960-9822(95)00105-9
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent regulation of cell growth by contactinhibin and the contactinhibin receptor

Abstract: Homeostasis is the net result of a highly balanced network of growth-stimulating and growth-inhibitory signals. We have shown that density-dependent inhibition of growth in vitro is mediated by the interaction of contactinhibin with a 92 kD plasma membrane glycoprotein, CiR, the contactinhibin-binding capacity of which is regulated by phosphorylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 29 publications
2
24
0
2
Order By: Relevance
“…Concomitantly, criss-crossed growth and the emergence of many foci, both being characteristic phenotypes of cultures of transformed cells, were observed. A twofold increase in cell density is the maximal value which can be achieved in con¯uent cultures of FH109 ®broblasts by impairing contactinhibition of growth, as shown in previous studies (Wieser et al, 1990;Gradl et al, 1995). Although we have not tested the hypothesis, according to the morphology of the cells in these cultures and in agreement with similar observations described in literature, it is suggested that in overcrowded cultures apoptosis takes place (Yasaka et al, 1996).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Concomitantly, criss-crossed growth and the emergence of many foci, both being characteristic phenotypes of cultures of transformed cells, were observed. A twofold increase in cell density is the maximal value which can be achieved in con¯uent cultures of FH109 ®broblasts by impairing contactinhibition of growth, as shown in previous studies (Wieser et al, 1990;Gradl et al, 1995). Although we have not tested the hypothesis, according to the morphology of the cells in these cultures and in agreement with similar observations described in literature, it is suggested that in overcrowded cultures apoptosis takes place (Yasaka et al, 1996).…”
supporting
confidence: 72%
“…In FH109 cells, human embryonal diploid lung ®broblasts (Wieser et al, 1985), contactdependent inhibition of growth is exclusively mediated by the interaction of two cell membrane proteins on adjacent cells, i.e. by the glycoprotein, contactinhibin (Wieser et al, 1990), which binds to its receptor referred to as contactinhibin receptor (Gradl et al, 1995).Cell-cell contacts were imitated by the addition of glutaraldehyde-®xed cells (in which contactinhibin remains active, as its growth inhibitory activity is mediated exclusively by its N-glycans not a ected by the ®xation process) to sparsely seeded ®broblasts in the presence of serum. In previous studies we have demonstrated that this system mimics physiological conditions concerning cell proliferation and differentiation which occur in con¯uent cultures (Wieser et al, 1985;Wieser and Oesch, 1986), thus enabling the study of early e ects of cell-cell contact-dependent signals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation assays control and recognition system. It either acts as a specific These were performed according to Gradl et al [9]. Briefly, 5X103 recognition site, e.g.…”
Section: Synthesis Of Sialic Acids Derivativesmentioning
confidence: 99%
“…We have shown previously that contact-deanti-rabbit antibodies (Sigma, Deisenhofen, Germany). Lectin-based pendent inhibition of the growth of non-transformed human detection of glycoprotein-bound sialic acids (all reagents from Boehringer Mannheim) was performed with digoxigenin-conjugated lectins fibroblasts is mediated by the plasma membrane glycoprotein followed by anti-digoxigenin antibodies according to the manufaccontactinhibin [8] and its receptor [9]. In addition, it has been turer's instructions.…”
Section: Synthesis Of Sialic Acids Derivativesmentioning
confidence: 99%